Pengaruh Content Marketing terhadap Customer Engagement Kopi Kenangan - Revida Mareta Herfi Ashari; Onny Fitriana Sitorus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The presence of the internet opens up opportunities for digital marketing and business owners compete to create interesting content to achieve sales targets. The purpose of this study was to determine the effect of Content marketing on Kopi Kenangan's Customer engagement and how big the influence of Content marketing on Kopi Kenangan's Customer engagement. The population in this study were the customers of Kopi Kenangan branch of the shophouse M. Toha, Tangerang City, which amounted to 175 customers. The method used is quantitative method with a total sample of 64 respondents. The technique of collecting samples using simple random sampling technique. The process of collecting data using a questionnaire via google form. Then the results were analyzed by correlation and regression analysis. The results showed that there was a significant influence between Content marketing on Kopi Kenangan Customer engagement. The effect of Content marketing on Customer engagement is 52.8%, while the remaining 47.2% is influenced by other variables that are not used in this study.